2010
DOI: 10.3892/ol_00000084
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metastasis from bile duct cancer of the ampulla is effectively controlled by multidisciplinary treatment including S-1, gemcitabine and bevacizumab: A case report

Abstract: Abstract. the liver is the most common site for recurrent metastases from bile duct cancer (BDc) in the ampullary area. However, the optimal chemotherapy regimen for recurrent hepatic metastases has not yet been established. An oral combined fluoropyrimidine drug, S-1 (tegafur, gimeracil and oteracil), has recently been introduced alone or in combination with gemcitabine for BDc. A 67-year-old man underwent a pancreaticoduodenectomy (PD) for early stage distal BDc in the ampullary area. A small hepatic metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[28][29][30][31][32][33][34][35] In Japan, gemcitabine has been mainly used to treat bile duct carcinoma and is now a key drug in the treatment of bile duct carcinoma. 36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation. 17,18 PDT induced NOZ cell death by apoptosis, detected in the Hoechst 33342-stained sections, in a light dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] In Japan, gemcitabine has been mainly used to treat bile duct carcinoma and is now a key drug in the treatment of bile duct carcinoma. 36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation. 17,18 PDT induced NOZ cell death by apoptosis, detected in the Hoechst 33342-stained sections, in a light dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%